PENGARUH FAKTOR PEMBENTUKAN CITRA TERHADAP OPINI PUBLIK PADA KANTOR PELAYANAN PAJAK PRATAMA TULUNGAGUNG - Rosiana Andhikasari; Geofakta Razali (Jurnal Komunikasi, 2018)
This study is aimed to investigate the effect of image formation factor components such as physical identity, non physical identity, organitation management, product quality, activity and relations. Variable X1 is physical identity, variable X2 is non physical identity, variable X3 is organitation management, Variable X4 is product quality, Variable X5 is  activity and relations, and variable Y is public opinion. This research belongs to quantitative research with corelational description. Sample employed here is 100 tax payers. In gathering the data, questionnaire is used and the result is counted by using likert scale. Moreover, to make the data valid, some tests are also used. They are validity test, reliability test, and classic assumption test that covers normality test and multicollinearity test. Furthermore, the data are analyzed by using double linier regression analysis. From the results of data analysis and discussion it was found that together the variables X1, X2, X3, X4, X5, and Y. The contribution of these five variables amounted to 59.1%, the remaining approximately 40.9% influenced by other factors besides these five variables. In this research note that the non physical identity’s variable is the most dominant variable affecting the public opinion. The existence of a good non physical identity of tax payer perceives the success of Tulungagung Tax Office. Effect of 59.1% can be assumed that the image formation is high, this means that Tulungagung Tax Office’s image can be said to succeed or be accepted by the public.Keyword: image formation factors, public opinion, tax office